Driving Performance Excellence At Tefa Tax Center: The Impact of Balanced Scorecard Implementation - Ambarkahi, Ratih Puspitorini Yekti; Chairina, Raden Roro Lia; Wardani, Dyah Kusuma; Andini, Paramita; Ismail, Andi Muhammad; Putra, Dhanang Eka (International Journal of Technology, Food and Agriculture, 2025)
In This study aims to examine the implementation of the Balanced Scorecard (BSC) as a performance management tool at the TEFA Tax Center, an entity operating in a dynamic taxation environment. The Balanced Scorecard was utilized to evaluate the organization's performance from four key perspectives: financial, customer, internal business processes, and learning and growth. The results indicate that the implementation of BSC at the TEFA Tax Center has led to significant improvements in various aspects of organizational performance. Operational efficiency increased by 23%, customer satisfaction rose by 18%, and employee engagement improved by 15%. These findings demonstrate that BSC is an effective tool in steering the organization's strategy towards sustainable performance enhancement. Recommendations from this study include further strengthening of internal business processes and enhancing human resource capabilities to support the long-term growth of the TEFA Tax Center. The implementation of BSC not only successfully improved current performance but also provided a solid foundation for future strategic planning.